2023
DOI: 10.3390/atmos14020376
|View full text |Cite
|
Sign up to set email alerts
|

Physical Explanation for Paradoxical Climate Change in Semi-Arid Inland Eurasia Based on a Remodeled Precipitation Recycling Ratio and Clausius–Clapeyron Equation

Abstract: Under global warming, the climate in semi-arid inland Eurasia (SAIE) has changed in an opposite manner, thereby seriously impacting the local ecological environment. However, the key influencing factors and physical mechanism remain inconclusive. In this paper, we remodel the precipitation recycling ratio (PRR) model to assess the contributions of moisture from different water vapor sources to local precipitation, analyze the characteristics of the PRR and precipitation in SAIE, and provide possible physical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Diba et al, [54] reported that the intensi cation of precipitation over West Africa is related to the warm extremes. According to the Clausius-Clapeyron equation, global warming has accelerated the local water cycle and increased advected moisture, leading to the intensi cation in precipitation extremes [55].…”
Section: Annual and Seasonal Dependent Changes In Precipitation Extremesmentioning
confidence: 99%
“…Diba et al, [54] reported that the intensi cation of precipitation over West Africa is related to the warm extremes. According to the Clausius-Clapeyron equation, global warming has accelerated the local water cycle and increased advected moisture, leading to the intensi cation in precipitation extremes [55].…”
Section: Annual and Seasonal Dependent Changes In Precipitation Extremesmentioning
confidence: 99%
“…Wang et al [5] partitioned the total precipitation into two components (namely, the local evaporation and external water vapor advection) and revised the precipitation recycling ratio model, which is used to assess the contributions of moisture from different water vapor sources to local precipitation in semi-arid inland Eurasia. It was found that the precipitation recycling ratio increased from 1970 to 2017, with obvious seasonality in this region.…”
mentioning
confidence: 99%